Analisis Pengujian Asap Aplikasi Web Direktori Eksportir - Haryaveda, Almeranda; Khairani, Rika (Cosmic Jurnal Teknik, 2024)
This research presents an analysis of initial testing (Smoke Testing) on a web application known as Directory Exporter. Smoke Testing is a type of performance testing designed to ensure that an application is fundamentally operational and can be run without failure in the early stages of development. In the context of this application, Smoke Testing was performed to evaluate the core functionality and basic capabilities of the Directory Exporter.Testing methods include testing key features such as directory export capabilities, operational continuity under light load conditions, and compliance with initial specifications. The results of this Smoke Testing analysis can provide insight into the initial stability of the application, identify potential problems or failures, and provide a basis for further development. This research contributes to the practical understanding of implementing Smoke Testing in web applications, with a special focus on the Directory Exporter.